EKSTRAK AIR BIJI PINANG (Areca Catechu L.) SEBAGAI PENGOMPLEKS UNTUK ANALISIS Fe (III) MENGGUNAKAN METODE PENCITRAAN DIGITAL - Ola, Pius D.; baun, Duwita N.; Lapailaka, Titus (Chemistry Notes, 2024)
A Research has been carried out on the utilization of areca seed aqueous extract as a complex for the analysis of iron(III) in aqueous media using digital imaging methods. In this study, the content of secondary metabolites in aqueous extract of areca nut was first determined, then an evaluation of performance parameters was carried out by analyzing iron(III) with aqueous extract of areca nut as the complexing agent, which was preceded by determining some of the optimum conditions for the formation of a complex between aqueous extract of areca nut–Fe (III). Areca seed water extract was then determined as an alternative reagent to determine the concentration of Fe(III) in real water samples using digital imaging by comparing this reagent with the standard KSCN reagent as the complexing agent. The results obtained showed that the correlation coefficient of areca seed water extract as complexing was 0.9741, which means that this method or reagent can be used as complexing agent for Fe(III) analysis in water. By comparing the extract and KSCN as a complex, it was found that the precision and accuracy of the two reagents were not significantly different in terms of precision but significantly different in terms of accuracy. When the areca seed water extract was applied to analyze Fe(III) in PDAM water and well water, % recovery was is still low and does not meet the % recovery requirements. This low recovery result indicates the amount of interfering substances in the water sample.